DISTRIBUSI LARVA NYAMUK DI DESA HENDA KABUPATEN PULANG PISAU KALIMANTAN TENGAH INDONESIA - Arif Rahman Jabal; Indria Augustina; Agnes Immanuela Toemon; Arini Ratnasari (BIOMA : JURNAL BIOLOGI MAKASSAR, 2024)
Mosquitoes are adaptable vectors that can survive in a variety of environments, and both tropical and subtropical regions of the planet are now home to them. Aedes sp. and Culex sp. mosquitoes are two vectors for the significant health issue known as arbovirus in humans. The purpose of this study is to map out the species distribution of mosquito larvae in Henda Village, Pulang Pisau Regency. This study has a cross sectional design and is a descriptive observational study. The Biomedical Laboratory, located in the Faculty of Medicine at Palangka Raya University, was used to conduct the sampling by looking for all mosquito larvae breeding places both inside and outside the home. Maps are used to visually represent data analysis and are displayed using descriptive distribution analysis. According to the study's findings, Ae. aegypti and Ae. albopictus larvae were discovered inside the home, and Ae. albopictus, Cx. Quinquefasciatus, and Cx. vishnui larvae were discovered outside. The breeding habitats for each species are unique. Through an integrated vector management scheme, the spread of arbovirus vectors discovered in Henda Village, Pulang Pisau Regency, can be managed.